Monomers for Adhesive Polymers, 10‐Synthesis, Radical Photopolymerization and Adhesive Properties of Methacrylates Bearing Phosphonic Acid Groups1. Issue 7 (29th August 2012) - Catel, Yohann; Fischer, Urs Karl; Moszner, Norbert
Abstract Syntheses of eight novel methacrylates bearing phosphonic acid groups were synthesized in three to five steps. The interaction of these monomers with hydroxyapatite was investigated using 13C‐NMR spectroscopy. Free radical homopolymerizations were carried out in a mixture ethanol/water (2.5/1, v/v) using 2, 2′azo(2‐methylpropionamidine) dihydrochloride as initiator. The copolymerization of these monomers with a mixture HEMA/GDMA (5/3, mol/mol) was investigated by photo‐DSC. Dentin shear bond strength measurements showed that 2‐methacryloyloxy‐3‐(1, 1, 2, 2‐tetrafluoroethoxy)propylphosphonic acid 4b, 2, 3‐dimethacryloyloxypropylphosphonic acid 18 and 3‐(methacryloyloxy)‐2, 2‐(di[(dihydroxyphosphoryl)methyl])propyl methacrylate 23 are promising candidates for dental adhesives. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>